Atlantic salmon (Salmo salar) under challenge: Heart rate and acceleration dynamics during exercise and stress - Agbeti, Wisdom E. K.; Palstra, Arjan P.; Black, Suzy; Magnoni, Leonardo; Lankheet, Martin; Komen, Hans (Frontiers in Physiology, 2025)
This study investigated the heart rate (HR) and acceleration (AC) dynamics of Atlantic salmon (Salmo salar) during a swim fitness test in a swim tunnel. Experimental fish were implanted with data loggers equipped with HR and AC sensors. These fish, and controls that were not implanted, were subjected to a swim-fitness test at incremental speeds from 0.2 to 1.0 m.s–1. Oxygen consumption (MO2) and locomotory behavior were monitored. Subsequently, these fish were subjected to a stress challenge test to further study the link between induced stress and HR and AC. When swimming from 0.2 to 1.0 m.s–1, the HR of implanted fish (N = 19) was high in the swim tunnels but remained stable between 82 and 84 beats per minute (bpm), despite significant increases in MO2, AC, tail beat frequency (TBF), and head width frequency (HWF). The stable HR observed was also reflected by HR explaining only ∼15% of the variation in MO2. MO2 of implanted fish increased from 238 to 343 mg.kg–1.h–1 when swimming from 0.4 to 1.0 m.s–1. With increasing swimming speeds, AC values of implanted fish increased from 16 to 27 milli-g and explained ∼40% of the variation in MO2. TBF increased linearly with swimming speed, and from 0.4 m.s–1 onward, it correlated strongly with MO2, similarly for HWF. Under controlled stress conditions, the HR values of fish were significantly higher than baseline conditions but similar during stress regardless of intensity. Also, AC showed similar stress peak patterns as HR. From these results, we conclude that the increased oxygen demand when swimming at increasing speeds is not met by increasing HR alone in Atlantic salmon. This supports the hypothesis that stroke volume plays an important role in boosting cardiac output. AC, in contrast to HR, showed a strong positive correlation with MO2 during swim-fitness tests and may serve as a reliable predictor of energy expenditure. TBF and HWF may also be useful predictors, but HR is not in Atlantic salmon. HR did show positive responses to induced stress but, similar to swimming, up to maximum values under 90 bpm.